Surgical Management of Facial Basal Cell Carcinoma: A Case Report Emphasizing the Need for Individualized Margin Assessment - Ulfa, Aulia; Subagio (HM Publisher, 2024)
Background: Basal cell carcinoma (BCC) is the most common form of skin cancer, and its incidence is steadily increasing. While surgical excision remains a cornerstone of BCC treatment, achieving complete tumor clearance while preserving healthy tissue and ensuring optimal cosmetic outcomes can be challenging, particularly in the facial region. This case report underscores the importance of individualized margin assessment in BCC excision. Case presentation: We present the case of a 52-year-old male with a nodular BCC on his left cheek. The lesion was excised with a 5mm margin under local anesthesia. Histopathological examination revealed incomplete excision, with residual tumor cells at the peripheral margin. The patient underwent a second excision with wider margins, achieving complete tumor clearance. Conclusion: This case highlights the limitations of standard margin guidelines in BCC excision. Factors such as tumor subtype, location, size, and patient characteristics should be considered when determining appropriate surgical margins. The use of intraoperative margin assessment techniques and adjuvant therapies may be beneficial in select cases.